Recloser Placement Optimization In The PDP-03 Radial Network Distribution System Using Ant Colony Optimization (ACO) - Bambang Winardi; Sudjadi Sudjadi (YCMM, 2022)
The increasing demand for electricity demanded that the power distribution system has a good reliability. To improve the reliability of electric power systems, PT. PLN Area Semarang use Recloser on the electricity network. Nowadays, the determination of recloser position is very important in reliability of electrical power system. Reliability index used in distribution systems are SAIFI and SAIDI. The value of SAIFI and SAIDI can be calculated from the outage time and the failure rate occurred in one year. Reliability can be concluded better if SAIFI and SAIDI smaller. This research aims to determine the optimal placement of recloser location on the electrical network in feeder PDP 03 Pudak Payung substation. The method used for the recloser location placement is Ant Colony Optimization (ACO) using Matlab Software R2014a. From simulation result, it can be concluded that the reliability value before and after placement recloser changed. SAIFI and SAIDI before recloser placement is 1.0172 times/year and 2.5435 hours/year. Optimal placement location for 1 recloser is at a location 4 with a value of SAIFI and SAIDI is 0.3361 times/year and 1.0456 hours/year. While for 2 reclosers is at a location 2 and 7 with a value of SAIFI and SAIDI is 0.26755 times/year and 0.86069 hours/year.